Human cloning : four fallacies and their legal consequences / Kerry Lynn Macintosh. - Macintosh, Kerry Lynn (Cambridge bioethics and law, 2013)
Since Dolly the sheep was born, controversy has swirled around the technology of cloning. We recoil at the prospect of human copies, manufactured men and women, nefarious impersonators and resurrections of the dead. Such reactions have serious legal consequences: lawmakers have banned stem cell research along with the cloning of babies. But what if our minds have been playing tricks on us? What if everything we thought we knew about human cloning is rooted in intuition rather than fact? Human Cloning: Four Fallacies and their Legal Consequences is a rollicking ride through science, psychology and the law. Drawing on sources ranging from science fiction films to the Congressional Record, this book unmasks the role that psychological essentialism has played in bringing about cloning bans. It explains how hidden intuitions have caused conservatives and liberals to act contrary to their own most cherished ideals and values.